A revision of the bathyal and abyssal necrophage genus Cyclocaris Stebbing, 1888 (Crustacea: Amphipoda: Cyclocaridae) with the addition of two new species from the Atlantic Ocean - Horton, Tammy; Thurston, Michael H. (Zootaxa, 2014)
Two new species of the deep-sea scavenging genus Cyclocaris (Crustacea: Amphipoda) are described from bathyal and abyssal depths in the North and tropical Atlantic Ocean, bringing the total number of species in the genus to four. An account of all four species is given and an updated key to the genus Cyclocaris is provided.